Math, asked by seemakelkar925, 2 months ago

the factorisation of p2 -9q2​

Answers

Answered by nivinnairmgmailcom
0

Answer:

Answer:

p²-10p+25 = (p-5)(p-5)

Step-by-step explanation:

Given quadratic expression:

p²-10p+25

Method 1:

p² - 10p + 25

= p²-2×p×5 + 5²

= (p-5)²

/* By algebraic identity:

\boxed {a^{2}-2ab+b^{2}=(a-b)^{2}}

a

2

−2ab+b

2

=(a−b)

2

*/

=(p-5)(p-5)

Therefore,

p²-10p-25 = (p-5)(p-5)

Method 2:

p²-10p-25

Splitting the middle term, we get

=p²-5p-5p-25

= p(p-5)-5(p-5)

= (p-5)(p-5)

Therefore,

p²-10p+25 = (p-5)(p-5)

Similar questions